(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article discusses the principles of argumentation and evidence in sources related to Islam, elucidating contemporary argumentation theory based on the presentation of viewpoints, actions, and moral virtues in the correct or incorrect light.